Decrease of Flavonol Synthase Enzymatic Activity in Ugni Molinae Turcz Due to the Domestication Process [Disminución de la Actividad Enzimática de la Flavonol Sintasa Debido Al Proceso de Domesticación en Ugni Molinae Turcz] - Urzua-Moll, A (Pontificia Universidad Catolica de Chile, Facultad de Agronomia e Ingenieria Forestal, 2019)
Flavonoid biosynthesis may be affected by plant domestication, with flavonoid production being reduced in proportion to the degree of domestication. In this context, kaempferol (3,4´,5,7-tetrahydroxyflavone) has been identified in the leaves of wild and cultivated Ugni molinae, a berry endemic to Chile. The biosynthetic pathway of kaempferol production begins with naringenin (4´,5,7-trihydroxyflavanone), which is converted to dihydrokaempferol (3,4´,5,7-tetrahydroxyflavanone), catalyzed by flavanone 3ß-hydroxylase (FHT) and then converted to kaempferol by a bifunctional enzyme called flavonol synthase (FLS). Therefore, our study aims to evaluate how FLS activity is affected in murtilla plants that are subjected to the domestication process. Kaempferol was quantified from methanolic extracts of leaf samples collected from both cultivated and wild U. molinae plants using high-performance liquid chromatography, and enzyme extraction was performed to determine FLS activity. The results showed that kaempferol concentration in wild plants from the Soloyo (0.14 μg g-1), Mehuín (0.18 μg g-1) and Queule (0.25 μg g-1) sampling areas was higher than in their cultivated counterparts. Our data are consistent with the FLS activity detected in samples obtained from Manzanal Alto (134.79 pKatal, Soloyo (96.48 pKatal), and Mehuín (119.97 pKatal). These samples also exhibited higher enzymatic activity than their cultivated counterparts. Together, these data suggest that FLS activity is negatively affected by the domestication process. © 2019, Pontificia Universidad Catolica de Chile, Facultad de Agronomia e Ingenieria Forestal. All rights reserved.